Culture and Politics in a Village of Immigrants from Djerba - Deshen, Shlomo; Jaeger, D. (Rural Settlements of New Immigrants in Israel, 1971)
Keywords: Judaïsme – Djerba

The Varieties of Abandonment of Religious Symbols: Changes in Ethnic Synagogue / גוונים של נטישת סמלים דתיים: שינויים בבית כנסת עדתי - Deshen, Shlomo (Megamot, 1971)
Taking the Weberian use of the term "secularization" as a point of departure, the author questions a recent identification of the term with the abandonment of religious beliefs per se. He shows that an abandoning of religious beliefs, which can be effected either through the eradication or the effacement (terms he posits in his typology of religious changes) of religious symbols, is not necessarily an index of secularization. The two concepts in turn are demonstrated to be distinct phenomena growing out of very different sociological conditions and circumstances. Three cases of symbolic change which occurred in a Djerban synagogue in Israel are discussed and the analysis is extended through a comparison with an African ritual. The three Djerban examples in the Israeli environment and the African ritual were found to be instances of effacement. In all four cases the very act of abandonment of the religious symbols, which was due to the fact that the particular symbols in question no longer conforms with the experiential situation of the actors, led to a reaffirmation of the symbols.
Keywords: Judaïsme – Djerba

Ethnicity and Citizenship in the Ritual of a Synagogue of Tunisian Immigrants / עדתיות ואזרחות בבית-הכנסת של עולי טוניסיה בישראל - Deshen, Shlomo (Megamot, 1971)
The paper examines the nature of the changes in ritual that occurred in an Israeli ethnic synagogue and their symbolic expressions, particularly the tension between citizenship and ethnicity. Certain events taking place in, or concerning, a particular synagogue were studied. The symbolic expression of the changes was found to be a means of communion of the worshipper with his new heterogeneous environment. The symbolic reference was now wider and the symbolic changes implied a shift in a relationship formerly obtained. In order to analyse the symbolic changes more definitely, the author developed a typology of religious changes comprising several types of symbolic changes of which the examples in this paper fall into the category of "innovation."
Keywords: Judaïsme – Djerba